ARS 01 : Avautuvia näköaloja. - Ai, Weiwei; Arriola, Magali; Bal-Blanc, Pierre; Bang Larsen, Lars; Beausse, Pascal; Bey, Dawoud; Bhabha, Homi; Buchloh, Benjamin H.D.; Ceron, Jaime; Daftari, Fereshteh; Dalmia, Yashodhara; De Baere, Bart; et al. (Helsinki : KIASMA Museum of Contemporary Art, 2001)
Aitken, Doug ; Amer, Ghada ; Arias, Carlos ; Braun, Matti ; Brotherus, Elina ; Cuenca Rasmussen, Lilibeth ; Dodiya, Anju ; Dube, Anita ; Durham, Jimmie ; Gaba, Meschac ; Geers, Kendell ; Hammons, David ; Hapaska, Siobhán ; Horelli, Laura ; Hakansson, Henrik ; Jaarsma, Mella ; Jermolaewa, Anna ; Julien, Isaac ; Junca, Humberto ; Jungen, Brian ; Jusidman, Yishai ; Kapoor, Anish ; Kay, Emma ; Kentridge, William ; Kim, Soo-Ja ; Kingelez, Bodys Isek ; Korkeila, Jukka ; Kuitca, Guillermo ; Kusolwong Surasi ; Langa, Moshekwa ; Lee, Bul ; Leonilson ; Liew, Kung Yu ; Lou, Liza ; Lu Qing ; Lundeby, Tor Magnus ; Meireles, Cildo ; Moffatt, Tracey ; Mondini-Ruiz, Franco ; Morelos, Delcy ; Murti, Krisna ; Mäetamm, Marko ; Männikkö, Esko ; Natesan, Shibu ; Neto, Ernesto ; Orozco, Gabriel ; Ortega, Damián ; Piñeyro, Maria Clara ; Rasdjarmrearnsook, Araya ; Rasmussen, Hans Hamid ; Renvall, Seppo ja Markus ; Rist, Pipilotti ; Rivera, Pablo ; Saebjörnsson, Egill ; Salcedo, Doris ; Sarcevic, Bojan ; Sarva, Sanna ; Sierra, Santiago ; Sikander, Shahzia ; Sotamaa, Kivi ; Holmstén, Markus ; Spero, Nancy ; Suda, Yoshihiro ; Tomaselli, Fred ; Tomic, Milica ; Tronvoll, Mette ; Utarit, Natee ; Walker, Kara ; Wang, Du ; Wong, Hoy Cheong ; Zakharov, Vadim ; Zhao Liang ; Ziura, Darius
Engels & Fins
ARS 01 : Unfolding Perspectives, KIASMA (Museum of Contemporary Art) Helsinki, 30.9.2001- 20.1.2002
boek